Nail Abnormalities In Genodermatose - Suci Widhiati; Retno Danarti; Cyntia Arum Budi Rustiawati (Rumah Sakit Umum Daerah Dr. Moewardi, 2026)
Introduction Nail abnormalities may serve as early indicators of various genodermatoses, either presenting in isolation or alongside systemic features. These abnormalities, though sometimes cosmetic, often hold significant diagnostic value, especially in inherited ectodermal disorders. Understanding the anatomy and embryology of the nail unit is crucial for identifying the origin and nature of such defects. Method This literature review was conducted by analyzing selected journal articles, case reports, and textbooks focusing on genodermatoses with distinct nail involvement. The analysis centered on the classification of nail abnormalities based on their anatomical origin: nail matrix, nail bed, or combined mesodermal-ectodermal defects. Results Findings revealed that nail abnormalities are prominent in several genodermatoses. Nail matrix defects are observed in congenital dyskeratosis, marked by nail dystrophy, leukoplakia, and mucocutaneous pigmentation. Nail bed defects, as seen in congenital pachyonychia and hydrotic ectodermal dysplasia, lead to thickened, dystrophic nails and associated skin changes. Combined mesodermal-ectodermal disorders, such as nail-patella syndrome, present with absent or hypoplastic nails alongside skeletal, renal, and ocular abnormalities. Each condition displayed specific nail manifestations that can aid early diagnosis. Discussion: The review emphasizes the importance of integrating knowledge of nail anatomy and development to differentiate between types of nail abnormalities. Identifying the anatomical origin aids in narrowing the differential diagnosis and can provide early clues to systemic genodermatoses, even before other clinical signs emerge. Conclusion: Nail abnormalities are important diagnostic markers in genodermatoses. Routine nail examination should be an integral part of dermatological assessments to facilitate early recognition and diagnosis of underlying genetic disorders.